Molecular mechanisms of osteosarcoma metastasis and possible treatment opportunities - Du, Xinhui; Wei, Hua; Zhang, Boya; Wang, Bangmin; Li, Zhehuang; Pang, Lon Kai; Zhao, Ruiying; Yao, Weitao (Frontiers in Oncology, 2023)
Metastasis is the main cause of death in osteosarcoma and there is no effective treatment currently available. In this study, we aimed to review the current findings regarding to the molecular mechanisms of metastasis and treatment options showing positive anti-metastasis results in preclinical studies in osteosarcoma. Alterations in the tumor cells such as the genomic and epigenomic changes, metabolic reprogramming, deregulated pathways, and transcription factors that had been reported to be involved in the regulation of osteosarcoma metastasis were reviewed. Besides, we also included the composition and functional state changes of the components within the tumor microenvironment. Key factors associated with osteosarcoma metastasis in the tumor microenvironment included infiltrating lymphocytes, macrophages, cancer-associated fibroblast, platelets, and extracellular components such as vesicles, proteins, or other secreted molecules. In addition, agents that inhibited osteosarcoma metastasis in preclinical studies are also summarized. The osteosarcoma metastasis is associated with various changes and reprogramming in tumor cells and the surrounding microenvironment. Novel therapy options are available and show promising results in preclinical studies.